Eating disorders in children and adolescents with type 1 diabetes mellitus - Piekarska, Małgorzata; Kasperski, Radosław; Pikulicka, Agata; Pacek, Katarzyna; Jedlina, Klaudia; Szulc, Izabela; Swacha, Weronika; Aghadi, Artur; Janczewska, Martyna; Kamińska, Izabela (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Eating disorders are an ever-growing problem, both in the general population and also in the population of pediatric patients with type 1 diabetes mellitus. However, for this specific group of patients, there is a twofold higher risk of developing eating disorders, the occurrence of additional distinct forms of these disorders, the so-called diabulimia - consisting of deliberate restriction of insulin delivery or skipping insulin doses, which can consequently lead to poor metabolic control of diabetes , and even threaten the lives of patients. The purpose of this work is to present the current state of knowledge on the diagnosis, prevention and treatment of eating disorders in children and adolescents with type 1 diabetes. The state of knowladge: The background of the onset of eating disorders in pediatric patients with type 1 diabetes mellitus includes the lowered self-esteem accompanying early adolescence, stress, excessive focus on external appearance, as well as difficulties in accepting the diagnosis and a rather strict dietary regime. Since the treatment of eating disorders is long and difficult, the most important goal becomes effective prevention and rapid selection of patients with a predisposition to develop such disorders. The first screening tools - SEEDS, m-SCOFF and DEPS-R questionnaires - have already been developed, and the effectiveness of therapy sessions aimed at this group of patients is also being studied. Summary: Therapy of eating disorders in patients with type 1 diabetes should be targeted at this specific patient population. It requires cooperation and communication of teams dealing separately with these diseases, education of the staff and their thorough knowledge of the background of the problem, prompt action and, above all, the development of specific guidelines for management, methods of prevention and the earliest possible start of treatment, which will also include the patient’s caregivers.